2019
DOI: 10.1016/j.juro.2018.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prostate Biopsy with or without Prebiopsy Multiparametric Magnetic Resonance Imaging for Prostate Cancer Detection: An Observational Cohort Study

Abstract: DISCLAIMER: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our subscribers we are providing this early version of the article. The paper will be copy edited and typeset, and proof will be reviewed before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to The Journal pertain. Embargo PolicyAll article content is under embargo until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
(35 reference statements)
2
21
0
Order By: Relevance
“…Conversely, PSA density (PSAd) <0.15ng/ml/ml was found to be a significant predictive factor in 8 studies [7][8][9]11,19,22,34,35]. The NPV of the combination of mpMRI and PSAd <0.15ng/ml/ml ranged from 84% to 100% in these studies.…”
Section: Clinical Factors and Psa Densitymentioning
confidence: 78%
“…Conversely, PSA density (PSAd) <0.15ng/ml/ml was found to be a significant predictive factor in 8 studies [7][8][9]11,19,22,34,35]. The NPV of the combination of mpMRI and PSAd <0.15ng/ml/ml ranged from 84% to 100% in these studies.…”
Section: Clinical Factors and Psa Densitymentioning
confidence: 78%
“…Bryant and colleagues suggested that a PSA density above 0.15 ng/ml/cc only acts a predictor of an increased likelihood of underlying csPCa in men with negative mpMRI when csPCa is defined as Gleason Grade Group 3-5 disease and/or tumour length ≥6 mm [28,57,58]. A prior negative biopsy may also a reassuring feature although we did not find a statistically significant difference in the summary NPVs between the primary biopsy (89%) and prior negative biopsy groups (93%) [61].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, performing systematic transrectal USguided biopsy after low-likelihood MRI findings in all men results in overdetection in about 18% (95% CI: 14%, 24%) of patients with ISUP grade group 1 disease (8,10,(35)(36)(37)(42)(43)(44). In other words, if systematic US-guided transrectal biopsies are performed after low-likelihood MRI, two men will be diagnosed with insignificant cancer for one man detected with an ISUP grade group 2 or greater cancer.…”
Section: Yield Of Systematic Transrectal Us Biopsy After Mri Reveals mentioning
confidence: 99%